THE EFFECTS OF DARK TRIAD (MACHIAVELLIANISM,NARCISSISM, PSYCHOPATHY) ON THE USE OF POWERSOURCES - (:unkn) unknown (My University, 2020)
Purpose of this research is to examine effects of dark triad personality traits (Machiavellianism,narcissism, and psychopathy) on the managers’ use of power sources. Data is collected from employeeswho work in various companies operating in different industries in Turkey through questionnaire surveys,using convenience sampling method for sampling. To measure Dark Triad personality traits Dirty Dozenscale which is developed by Jonason and Webster (2010) is used, to measure power sources InterpersonalPower Inventory (IPI) which is developed by Raven et al. (1998) is used. Exploratory Factor Analysis isconducted to dirty dozen and IPI scales which returned three and ten items respectively. Correlation andmultiple regression analyses are conducted using all items, lead to find out moderate correlations betweendark triad constructs, positive correlations between dark triad and personal coercion, impersonal coercion,legitimacy-position and negative correlations between legitimacy-dependence and information powersources. Also, regression analyses showed psychopathy and Machiavellianism has negative effect oninformation and legitimacy-dependence as well as positive effect on the use of impersonal coercion.Results indicated positive effect of narcissism and negative effect of psychopathy on the use of expertpower. All three constructs are founded to have a positive effect on the use of personal coercion. Darktriad constructs are founded not to have an effect on personal reward, impersonal reward, legitimacyequity and legitimacy- reciprocity power sources. The implications of the results are discussed and futureresearch areas are suggested.

Bu çalışmanın amacı, karanlık üçlü kişilik özelliklerinin (narsisizm, psikopati, makyavelizm) yöneticilerin güç kaynakları kullanımına etkilerinin incelenmesidir. Araştırma verisi Türkiye’de farklı sektörlerde çalışmakta olan kişilere kolayda örnekleme yöntemi kullanılarak anket uygulanması ile toplanmıştır. Karanlık üçlü için Jonason ve Webster tarafından 2010 yılında geliştirilmiş olan Karanlık Üçlü Ölçeği, güç kaynaklarını ölçmek için ise Raven ve diğerleri tarafındn 1998 yılında geliştirilen IPI ölçeği kullanılmıştır. Ölçeklere keşfedici faktör analizi uygulanmış, sırasıyla üç ve on boyut elde edilmiştir. Akabinde korelasyon ve çoklu doğrusal regresyon analizleri yapılarak araştırmanın hipotezi sınanmıştır. Araştırma sonuçları, karanlık üçlü yapıları arasında ortalama düzeyde bir korelasyon bulunduğuna, üçlü ile kişisel cezalandırıcı, kişisel olmayan cezalandırıcı, yasal-pozisyon güç kaynakları arasında pozitif korelasyon bulunduğuna, bilgi ve yasal-bağımlılık kaynakları arasında ise negatif korelasyon bulunduğuna işaret etmektedir. Ayrıca regresyon analizleri psikopati ve makyavelizmin bilgi ve yasal-bağımlılık güç kaynakları üzerinde negatif etkisinin, kişisel olmayan cezalandırıcı güç kaynağı üzerinde ise pozitif etkisinin bulunduğunu göstermektedir. Öte yandan bulgular narsisismin uzmanlık gücü üzeride pozitif, psikopatinin ise negatif etkisi olduğunu göstermektedir. Karanlık üçlünün tüm alt boyutlarının kişisel cezalandırıcı güç üzerinde pozitif etkiye sahip olduğu, kişisel ödüllendirici, kişisel olmayan ödüllendirici, yasal-eşitlik ve yasal-karşılıklılık kaynakları üzerinde ise istatistiksel olarak anlamlı bir etkisinin bulunmadığı tespit edilmiştir. Araştırma bulguları sonuç bölümünde tartışılmıştır.
KARANLIK ÜÇLÜNÜN (MAKYAVELIZM, NARSISIZM, PSIKOPATI) GÜÇ KAYNAKLARI KULLANIMI ÜZERINDEKI ETKILERI